MEDIA KOMUNIKASI POLITIK CALEG TERPILIH DALAM BERKAMPANYE (Studi Deskriptif Kualitatif Tentang Pemilu Legislatif di Kabupaten Sragen) - Maya Sekarwangi & Siswanto, Risqi Arum Sari (Transformasi, 2014)
Using print media in political campaigns conducted by members of the Sragen’s legislature parliament include the installation of banners , posters , billboards , visits to community meetings , visits to homes directly ( door to door ) and meetings with farmer groups and local youth community have a strategic role in conveying a political message to the public. The print media are more effectively used in campaigns because every day the public will see posters mounted , supported by visits to the community or farmer associations and local youth community might prove more effective than a candidate who uses electronic media via radio . The strength of print media in political campaigns of Sragen’s legislative parliament is the print media does not take long to introduce the program, vision, mission to the community at the same time elected legislators can interact directly with the public and it can not be done using electronic media , where people can not interact directly or face to face either with a campaign team and the candidates themselves . Key Words: regulations, policy, communication, index